Asymptomatic School-Aged Children Are Important Drivers of Malaria Transmission in a High Endemicity Setting in Uganda. (17th May 2022) - Rek, John; Blanken, Sara Lynn; Okoth, Joseph; Ayo, Daniel; Onyige, Ismail; Musasizi, Eric; Ramjith, Jordache; Andolina, Chiara; Lanke, Kjerstin; Arinaitwe, Emmanuel; Olwoch, Peter; Collins, Katharine A; et al.
Abstract: Achieving malaria elimination requires a better understanding of the transmissibility of human infections in different transmission settings. This study aimed to characterize the human infectious reservoir in a high endemicity setting in eastern Uganda, using gametocyte quantification and mosquito feeding assays. In asymptomatic infections, gametocyte densities were positively associated with the proportion of infected mosquitoes (β = 1.60; 95% CI, 1.32–1.92; P  < .0001). Combining transmissibility and abundance in the population, symptomatic and asymptomatic infections were estimated to contribute to 5.3% and 94.7% of the infectious reservoir, respectively. School-aged children (5–15 years old) contributed to 50.4% of transmission events and were important drivers of malaria transmission. Abstract : In an area of intense malaria transmission in Uganda, school-aged children (5–15 years old) and asymptomatic infections were identified as major contributors to the malaria human infectious reservoir and could be considered as important targets for malaria control interventions.